Calcium Hydroxide Induced Apexification in an Immature, Non-Vital Permanent Tooth – A Case Report (London Journal of Medical and Health Research, 2026)
The purpose of the present manuscript is to show case successful formation of apical barrier in an immature young permanent tooth following dental trauma using calcium hydroxide as an intra-canal medicament. Following 9 month follow-up, apical barrier formation and absence of periapical radiolucency was evident on intraoral periapical radiographic examination with clinical absence of signs and symptoms. This case report strongly confirms that calcium hydroxide still remains as age old, gold standard medicament in inducing apical barrier formation thereby facilitating a dental practitioner to perform smooth root canal treatment.
Keywords: apexification; apical barrier formation; blunder bus canal; calcium hydroxide; immature; non-vital tooth